Development and evaluation of collagen peptides from milkfish (Chanos chanos) scale waste as a potential biopreservative candidate - Sudrajat Sugiharta; Monica Yashna Kusuma Adi Saputra; Iin Lidia Putama Mursal; Dhea Ananda; Aditya Maulana Akbar; Dini Hakiki; Muhammad Rizki Aditya (Universitas Ahmad Dahlan, 2026)
The escalating health concerns associated with synthetic food preservatives necessitate the exploration of biocompatible, natural alternatives. With mounting toxicological evidence linking these chemical agents to severe metabolic and neurological disorders, the transition toward safe, sustainable marine biopolymers has become a public health interest. This study aimed to valorize milkfish (Chanos chanos) scales by extracting collagenous peptides and evaluating their efficacy as a potential biopreservative candidate. An extraction protocol utilizing 1 M acetic acid with varying pepsin concentrations (1%, 2%, and 3%) was employed. The highest yield (1.65%) was achieved using a 1% pepsin treatment (A1P1), producing collagen peptides with favorable physicochemical properties complying with national standards: 73.92% crude protein, stable near-neutral pH (6.73), and minimized moisture, ash, and lipid contents. In vitro antibacterial evaluations via the disk diffusion method revealed a paradoxical dose-response; the lowest peptide concentration (0.05%) exhibited significant activity against the Gram-negative pathogen Escherichia coli (20.70 mm inhibition zone), outperforming the 0.1% synthetic benzoic acid control. Conversely, efficacy against Gram-positive Staphylococcus aureus remained weak, likely limited by the bacteria's dense peptidoglycan barriers. These findings indicate the viability of milkfish scale collagen as a sustainable, potential biopreservative candidate that advances circular economy paradigms, although further molecular characterization and real-food matrix applications are required for future commercial formulation.